Genome-wide analysis of the TIFY family and function of CaTIFY7 and CaTIFY10b under cold stress in pepper (Capsicum annuum L.) - Wang, Xiaodi; Li, Ning; Zan, Tianxiang; Xu, Kai; Gao, Shenghua; Yin, Yanxu; Yao, Minghua; Wang, Fei (Frontiers in Plant Science, 2023)
TIFY [TIF(F/Y)XG] proteins are a plant particular transcription factor family that regulates plant stress responses. Therefore, to fill this gap, we investigated CaTIFY genes in pepper.Gene structure and conserved motifs of the pepper TIFY gene family were systematically analyzed using sequence alignment analysis, Cis-acting element analysis, transcriptomic data, and RT-qPCR analysis, and their expression patterns were further analyzed using Virus-Induced Gene Silencing (VIGS) and cold stress reactive oxygen species (ROS) response. We identified 16 CaTIFY genes in pepper, which were dispersed among seven subgroups (JAZI, JAZII, JAZIII, PPD, TIFY, and ZIM/ZML). Several CaTIFY members had stress-related harmonic-responsive elements, and four (CaTIFY7, CaTIFY10b, CaTIFY1b, and CaTIFY6b) had low-temperature-responsive elements. Transcriptomic data and RT-qPCR analysis revealed that the TIFY genes in pepper displayed different expression patterns in the roots, stems, leaves, flower fruits, and seeds. In particular, CaTIFY7 was highly expressed in young leaves, and CaTIFY10b was highly expressed in roots. CaTIFYs participated in the regulation of several different abiotic stresses and CaTIFY7 and CaTIFY10b were significantly induced by cold stress. Additionally, Virus-Induced Gene Silencing (targeting CaTIFY7 and CaTIFY10b) resulted in plants that were sensitive to cold stress. Conversely, overexpression of CaTIFY7 and CaTIFY10b enhanced plant cold tolerance by promoting the expression of genes related to cold stress and the ROS response. CaTIFY7 and CaTIFY10b interacted with themselves and CaTIFY7 also interacted with CaTIFY10b in the yeast two-hybrid (Y2H) system. Our data provide a basis for further analysis of the role of pepper TIFY genes in cold-stress responses in the future.